2014
DOI: 10.1186/1475-2891-13-66
|View full text |Cite
|
Sign up to set email alerts
|

Chocolate flavanols and skin photoprotection: a parallel, double-blind, randomized clinical trial

Abstract: BackgroundSolar ultraviolet (UV) radiation has deleterious effects on the skin, including sunburn, photoaging and cancer. Chocolate flavanols are naturally-occurring antioxidant and anti-inflammatory molecules that could play a role in preventing cutaneous UV damage. We investigated the influence of 12-week high-flavanol chocolate (HFC) consumption on skin sensitivity to UV radiation, measured by minimal erythema dose (MED). We also evaluated skin elasticity and hydration.MethodsIn this 2-group, parallel, doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 45 publications
2
23
1
Order By: Relevance
“…LF group showed a small increase, but statistically significant, compared epicatechin dosage in plasma at weeks 6, 9 and 12 compared to baseline. The HF Group was marked by more considerable increases of epicatechin in plasma (Mogollon et al, 2014).…”
Section: Flavanol Cocoa (Catechin and Epicatechin)mentioning
confidence: 93%
“…LF group showed a small increase, but statistically significant, compared epicatechin dosage in plasma at weeks 6, 9 and 12 compared to baseline. The HF Group was marked by more considerable increases of epicatechin in plasma (Mogollon et al, 2014).…”
Section: Flavanol Cocoa (Catechin and Epicatechin)mentioning
confidence: 93%
“…The high flavanol chocolate was found to significantly increase net elasticity (Ur/Ue ratio) compared to the low flavanol chocolate, although not all measures of elasticity significantly differed between groups (Mogollon et al . ).…”
Section: Popular Nutraceutical Ingredients and Skin Ageingmentioning
confidence: 97%
“…et al (2001),Rhodes et al (2003),Heinrich et al (2006),Kasai et al (2006),Peguet-Navarro et al (2008),Williams et al (2009), Bouilly-Gauthier et al (2010,Heinrich et al (2011),Rhodes et al (2013),Pilkington et al (2014),Mogollon et al (2014), Farrar et al (2015,Yoon et al (2016),Zmitek et al (2017) Commonly used to look at efficacy of: green tea extract, pomegranate extract, carotenoids, fish oil, cocoa flavanols, probiotics, co-enzyme Q10ElasticityThe resistance of skin to suction (viscoelasticity) and the ability of skin to return to its original position (biological elasticity) can be measured using a cutometer Measurements taken include skin extensibility (Ue), delayed distention (Uv), final deformation (Uf) and immediate retraction (Ur). Ratios are also reported.…”
mentioning
confidence: 99%
“…In three randomized controlled studies, daily intake of high flavanol cocoa (HFC, more than 329 mg) and low flavanol cocoa (LFC, less than 30 mg) for 3 months were compared. All studies revealed an increase in MED or a decrease in UIE intensity following HFC ingestion [16][17][18]. Only one research reported increasing MED in LFC administration [16].…”
Section: Theobroma Cacaomentioning
confidence: 99%
“…All studies revealed an increase in MED or a decrease in UIE intensity following HFC ingestion [16][17][18]. Only one research reported increasing MED in LFC administration [16]. Moreover, skin elasticity and hydration were improved after HFC administration [16,18].…”
Section: Theobroma Cacaomentioning
confidence: 99%